Learning to teach with a classroom simulator - Gibson, David; Kruse, S. (AACE, 2012)
A classroom simulator - simSchool - offers a new paradigm for teacher education based in self-direction & personal validation in a complex but repeatable practice environment, supported by emergent interdisciplinary knowledge concerning the unique affordances of digital media assessment and social media.